Perceptual MAP of Online Fashion Store - Prasetya, Cindy; Iskandar, Budi Permadi (Journal of Business and Management, 2014)
The main theme of this research is Fashion Marketing and focus on customers-driven marketing strategy and brand image marketing strategy. The purpose of this research is to map customers-based positioning of local online fashion companies, which are benchmarked by global leading fashion brands. In this research, multidimensional scaling is being applied to process the data. Multidimensional scaling is purposed to map the ordinal data and determine its spatial configuration based on the similarities and dissimilarities. The data applied in this research are obtained from 60 respondents in 600 cases with 10 brands as its objects. According to Tucker’s Coefficient of Congruence, the factors in the questionnaire are virtually identical but nevertheless, the questionnaire is good based on the normalized stress testKeywords: Consumer, Fashion, Local, Online, Marketing, Strategy, Target